ANALISIS PENGEMBANGAN SEKTOR PARIWISATA KABUPATEN SUMBAWA - Ade Dewi Yulianti; Aris Soelistyo; Setyo Wahyu Sulistyono (Program Studi Ekonomi Pembangunan, 2021)
By utilizing exotic resources, making tourism places as known as the tourism sector in Sumbawa Regency that plays an important role in regional economic growth in Sumbawa Regency, not only playing a role in the economy but also the tourism sector as an additional source of income, both regional income and influential. on per capita income, this study aims to determine the strategy in seeking the development of the tourism sector of Sumbawa Regency, hotel tax, restaurant tax, entertainment tax, number of tourist visits, Micro, Small and Medium Enterprises (MSMEs) and Tourism Sector Manpower as independent variables. how is the development of Sumbawa district in the tourism sector, where the tourism sector is in the form of tourism sector income (the contribution of the tourism sector) as the dependent variable with the 2015-2019 research period. The research analysis uses panel data analysis with the Fixed-Effects (FE) approach. The estimation results show that hotel taxes, the number of tourist visits, MSMEs, and workers receive H0, which has increased and has a positive and significant influence on Sumbawa Regency in the tourism sector.